A case of duodenal atresia - Parma Umi Asnil; Sumanto Sumanto; Darwin Arsjad (Indonesian Pediatric Society, 1973)
Congenital atresia of the intestines and colon is an uncommon malformation in which there is complete obstruction of the alimentary tract. It rapidly produces vomiting, severe dehydration, and possibly rupture of the blind intestine. If no surgical relief is given, death supervenes in most cases in the first week of life, but surgical therapy is followed by high mortality. Prompt recognition of the obstruction and immediate operation give the only hope of survival (Gross, 1953).Vidal (1915) as cited by Young (1966) is the first who report the successful treatment of neonatal duodenal obstruction.